On Not Misreading Origen. (28th October 2021) - Williams, Rowan
Abstract: This essay draws together points from earlier short studies in an attempt to clarify why and how Origen was misunderstood by both his critics and his defenders in the fourth century. We need to identify what he is seeking to avoid saying: his concern is to rule out any kind of divisibility in the divine life, and also to challenge any suggestion that the effect of the Logos's activity in creation is in any way limited. These concerns explain why he is critical of widely received exegetical consensus on some passages when such consensus gives hostages to the views he seeks to exclude. Furthermore, this must all be understood in the context of a model of scriptural exegesis which is both deeply informed by the literary scholarship of the day and shaped by the understanding of exegesis as a 'priestly' task of induction into the divine life of the Logos.